Spring departure date, not en route conditions, drive migration rate and arrival timing in a long-distance migratory songbird - Turcotte-van de Rydt, Christophe; Muthukumarana, Saman; Fraser, Kevin C. (Frontiers in Bird Science, 2023)
Long-distance avian migrants are threatened by a rapidly changing environment, which can induce a mismatch between favorable environmental conditions and the timing of breeding. Therefore, migratory birds must rely on phenotypic plasticity within migration timing to remain synchronized with earlier occurring resources over the shorter term. However, how this plasticity responds to en route environmental factors and whether or not it may allow migratory birds to remain synchronized with advancing springs is largely unknown. The objective of this study was to investigate how extrinsic factors, such as those related to the weather (e.g., temperature, precipitation, and wind speed) and daylength experienced along spring migration routes, and intrinsic factors, such as sex and age, migration departure date from wintering grounds, and migration destination (i.e., breeding site), influence the migration rate and spring arrival date at breeding grounds in purple martins (Progne subis). We investigated arrival timing and rate using 307 individual migration tracks sampled across the birds’ eastern breeding range. We found that the departure date and total stopover time explained most of the variation in migration rate, with birds departing later traveling faster but taking more stopover days, leading to a slower overall migration rate. To a lesser extent, facilitating southern winds and lower precipitation also induced a faster migration rate. We found that birds with a faster migration rate arrived earlier at their breeding sites. We also found that female birds traveling to more northern breeding sites arrived earlier than male birds, and that they migrated at a faster rate. Overall, our results suggest that the migration rate may be most impacted by intrinsic factors tied to spring departure dates that are aligned with the phenology of breeding sites rather than by conditions experienced en route. These findings support growing evidence that selection for spring departure date may be needed for the advancement of spring arrival date to match advancing springs with climate change. Future research investigating how environmental conditions at stopovers contribute to the overall migration rate would provide further insight into the factors influencing migration timing.